Using Metabolomics to Investigate Biomarkers of Drug Addiction. Issue 2 (February 2018) - Ghanbari, Reza; Sumner, Susan
Abstract : Drug addiction has been associated with an increased risk for cancer, psychological complications, heart, liver, and lung disease, as well as infection. While genes have been identified that can mark individuals at risk for substance abuse, the initiation step of addiction is attributed to persistent metabolic disruptions occurring following the first instance of narcotic drug use. Advances in analytical technologies can enable the detection of thousands of signals in body fluids and excreta that can be used to define biochemical profiles of addiction. Today, these approaches hold promise for determining how exposure to drugs, in the absence or presence of other environmentally relevant factors, can impact human metabolism. We posit that these can lead to candidate biomarkers of drug dependence, treatment, withdrawal, or relapse. Highlights: With modern technology, it is feasible to determine the exposome of an individual and to assess how multiple types of exposure (e.g., environmentally relevant chemicals, tobacco products, or clinically relevant drugs) contribute to addiction, withdrawal, and adverse health outcomes associated with substances of abuse. The use of metabolomics in well-designed studies of opiate addiction may enable the identification of targets for pharmacological and/or nutritional intervention. Metabolomics is an ideal approach to study human individuality in response to both drug exposure and treatment.